2019
DOI: 10.1155/2019/7838195
|View full text |Cite
|
Sign up to set email alerts
|

Gas6/TAM Receptors in Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a multiorgan autoimmune disease associated with impaired immune system regulation. The exact mechanisms of SLE development remain to be elucidated. TAM receptor tyrosine kinases (RTKs) are important for apoptotic cell clearance, immune homeostasis, and resolution of immune responses. TAM deficiency leads to lupus-like autoimmune diseases. Activation of TAM receptors leads to proteolytic cleavage of the receptors, generating soluble forms of TAM. Circulating TAM receptors h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 84 publications
0
35
0
Order By: Relevance
“…These convergent functions may be implicated in the development of autoimmune disorders. For instance, the TAM system has been related to multiple sclerosis, an autoimmune demyelinating disease [ 60 ] and systemic lupus erythematosus (SLE), a chronic autoimmune disease that is associated to defective clearance of apoptotic cells [ 61 ]. Therefore, impaired TAM activity could trigger these disorders by promoting autoantigen exposure and reducing self-tolerance, leading to an uncontrolled immune response [ 14 , 62 , 63 ], as recently reviewed [ 64 , 65 ].…”
Section: Tam Receptor Functionsmentioning
confidence: 99%
“…These convergent functions may be implicated in the development of autoimmune disorders. For instance, the TAM system has been related to multiple sclerosis, an autoimmune demyelinating disease [ 60 ] and systemic lupus erythematosus (SLE), a chronic autoimmune disease that is associated to defective clearance of apoptotic cells [ 61 ]. Therefore, impaired TAM activity could trigger these disorders by promoting autoantigen exposure and reducing self-tolerance, leading to an uncontrolled immune response [ 14 , 62 , 63 ], as recently reviewed [ 64 , 65 ].…”
Section: Tam Receptor Functionsmentioning
confidence: 99%
“…We also investigate the function of different genes involved in the duplicated 13q22-q34 region and their possible role on both immunological functions and coagulation pathways. Some of these genes are involved in the coagulation pathway as the Z protein ( PROZ ) and the Growth arrest-specific gene 6 protein ( GAS6 ) genes, known to play an important role in regulating blood coagulation and in the regulation of thrombotic responses as well as in cerebral haemorrhage, thrombosis and in the genetic susceptibility of systemic lupus erythematosus (SLE) [ 5 , 10 , 11 , 12 , 13 , 14 , 15 ]. In our patient cerebral vasculitis findings associated to LAC positivity could be related also to the involvement of the TNFSF13B (named also B lymphocyte stimulator, BLyS ) gene that encodes a cytokine that belongs to the tumor necrosis factor (TNF) ligand family and it is reported to be significantly increased in the primary antiphospholipid syndrome (PAPS) and in LES, as confirmed by an animal model study [ 16 , 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…TAM and their ligands are involved in recognition and removal of apoptotic cells by macrophages 71 . It was demonstrated that Mer is highly expressed on renal ECs, 72 and it promotes phagocytosis of apoptotic debris and inhibits cytokine production, maintaining an immune homeostasis 73 . Mer‐KO mice have impaired capability of properly removing apoptotic cells and develop lupus‐like autoimmunity and nephritis 73,74 .…”
Section: Pharmacological Endothelial Targets In Sle and Lnmentioning
confidence: 99%
“…It was demonstrated that Mer is highly expressed on renal ECs, 72 and it promotes phagocytosis of apoptotic debris and inhibits cytokine production, maintaining an immune homeostasis 73 . Mer‐KO mice have impaired capability of properly removing apoptotic cells and develop lupus‐like autoimmunity and nephritis 73,74 . On the other hand, Axl and its ligand Gas6 become upregulated only under inflammatory stimulation and promote mesangial proliferation 73,74 .…”
Section: Pharmacological Endothelial Targets In Sle and Lnmentioning
confidence: 99%
See 1 more Smart Citation